2020
DOI: 10.1097/pq9.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Safe Sleep Counseling by Pediatricians through a Quality Improvement Learning Collaborative

Abstract: Background: Approximately, 3,500 infants die annually from sleep-related infant deaths in the United States. We sought to improve pediatricians’ counseling on safe sleep from birth through 6 months of age through a virtual quality improvement learning collaborative (QILC). Our aim was appropriate screening, counseling, and documentation of safe sleep advice in 75% of eligible patient encounters after the QILC. Methods: We formed a 9-month QILC for inpatient and outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Representatives from seven clinic sites participated in bimonthly meetings for 12 months and received clinic-specific coaching on closing gaps in quality measures. Similar to other virtual QICs,15 24–26 participants found the web-based modality acceptable and useful.…”
Section: Discussionmentioning
confidence: 64%
“…Representatives from seven clinic sites participated in bimonthly meetings for 12 months and received clinic-specific coaching on closing gaps in quality measures. Similar to other virtual QICs,15 24–26 participants found the web-based modality acceptable and useful.…”
Section: Discussionmentioning
confidence: 64%
“…18 Scott et al also demonstrated that a facilitated, virtual quality improvement learning collaborative was an effective way to improve safe sleep counseling among a diverse group of pediatric practices. 19…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al demonstrated that a quality improvement collaborative improves screening, counseling, and documentation of anticipatory guidance during newborn nursery and primary care visits. 22 A similar approach could improve screening and education for at-risk infants in the hospital setting. Further research is needed to determine if an optimal implementation strategy could be generalized across institutions, perhaps by combining the most successful aspects of several different care bundles.…”
Section: Discussionmentioning
confidence: 99%
“…While safe sleep education should occur during prenatal and infant primary care visits, additional education and modeling in the hospital setting may reinforce safe sleep practices at home. The Infant Care Practices Study demonstrated that maternal adherence to a safe sleep environment declines over time, measured at 1 month, 3 months, and 6 months postdelivery, 23 suggesting that postnatal education and modeling could influence the sleep environment. In addition, a safe sleep bundle in the NICU can improve safe sleep environments for hospitalized infants and improve the sleep environment postdischarge.…”
Section: Discussionmentioning
confidence: 99%